Uremic tumoral calcinosis, report of a rare case at King Chulalongkorn Memorial Hospital - Kumtornrut, Chanat; Numkarunarunrote, Numphung; Rerknimitr, Pawinee (Chulalongkorn Medical Journal, 2023)
Uremic tumoral calcinosis is primarily found in patients with chronic kidney disease (CKD) or end-stage renal disease (ESRD). Its clinical and radiologic presentations are highly characteristic. We herein report a case of a 33-year-old Thai male with ESRD and tertiary hyperparathyroidism. He presented with multiple cystic nodules on the right shoulder, hands, and feet without causing joint destruction for 2 years. The plain radiographs of the right shoulder and hands showed the pathognomonic “sedimentation sign”. The patient underwent subtotal parathyroidectomy, as a result, the masses significantly decreased in size 3 months later. This case should increase the awareness among dermatologists and internists in the diagnosis and management of this rare disorder.